(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Rectovaginal space hematoma following vaginoplasty is a rare complication that can lead to serious morbidity and disability. In the literature, reported cases remain few, especially in low-income countries where cosmetic gynecology consultations are increasing. Case presentation: We present a case of extensive rectovaginal space hematoma presenting with urine retention following vaginoplasty. The patient had anemia, hypotension, tachycardia, vulval swelling, and a suprapubic mass from the overdistend bladder. She was surgically managed and did well postoperatively. Conclusion: Rectovaginal space hematomas are rare and associated with significant morbidity if inappropriately managed. Cosmetic gynecological surgeons should be aware of this complication.